THE EFFECT OF ENTREPRENEURIAL EDUCATION AND EXPERIENTIAL LEARNING ON ENTREPRENEURIAL INTENTION MEDIATED BY TEACHING FACTORY (TEFA) - Fatmawati, Kurnia; Kusdiyanti, Heny; Sumarsono, Hadi (PT. BATARI EDU CALYA, 2023)
The purpose of this research is to look at students' entrepreneurial intentions. The focus of this research is to examine the influence of entrepreneurial education and experiential learning on students' entrepreneurial intentions. In this research, the teaching factory is positioned as a mediator of the relationship between entrepreneurial education, experiential learning, and entrepreneurial intention. This research uses a descriptive design using quantitative research methods. The respondents of this research are students from State Middle Schools throughout Mojokerto Regency with Fashion Design Departments, namely SMKN 1 Sooko and SMKN Jatirejo, and have received entrepreneurship lessons and have implemented the Teaching Factory Learning Model, namely classes XI and XII majoring in fashion design. The research sample consisted of 237 students who underwent an online survey and calculated using structural equation modeling (SEM). The findings from this study show that there is a direct and significant positive effect between Entrepreneurial Education towards Teaching Factory (Tefa), as well as there effect positive directly and significantly between Experiential Learning to Teaching Factory(Tefa). However, there is a direct and significant negative influence between Teaching Factory(Tefa) to Entrepreneurial Intention. Apart from that, there is a direct and significant positive effect between Entrepreneurial Education on Entrepreneurial Intention, And there is a direct and significant effect between Experiential Learning on Entrepreneurial Intention. However The research results indirectly show that Teaching Factory(Tefa) failed to play a role in mediating the relationship between entrepreneurial Education, experiential learning toward entrepreneurial intention